2013
DOI: 10.1108/vine-11-2011-0058
|View full text |Cite
|
Sign up to set email alerts
|

Perceived environmental uncertainty and competitive intelligence practices

Abstract: Purpose -The study aims to examine the current state of competitive intelligence practices in Malaysian public listed companies, the perception of environmental uncertainty and the link between the two concepts. Design/methodology/approach -The data were collected from 123 public listed companies via mail questionnaire survey. Variables and measurement were adopted from prior empirical studies, specifically from Daft, Sormunen and Parks. Findings -Generally, the current state of competitive intelligence practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The results of this study are supported by previous research, such as Hadj (2020); Harash (2015); Hosseini & Sheikhi (2012); Junquera & Barba-Sánchez (2018); Kim & Choi (2016); Poulis & Wisker (2016); Salem (2019); Widyaningdyah & Aryani (2016); Yap et al (2013) that found a positive and significant effect between environmental uncertainty and competitiveness. Likewise, environmental uncertainty has a positive and significant influence on the performance of fishing companies, consistent with research (Allegrini & Monteduro, 2018;Darvishmotevali et al, 2018;Gupta & Gupta, 2020;Harash, 2015;Hengky et al, 2018;Hosseini & Sheikhi, 2012;Kafetzopoulos et al, 2019;Mohammad, 2019;Poulis & Wisker, 2016;Widyaningdyah & Aryani, 2016;Wong et al, 2011).…”
Section: Discussion and Research Implicationssupporting
confidence: 90%
“…The results of this study are supported by previous research, such as Hadj (2020); Harash (2015); Hosseini & Sheikhi (2012); Junquera & Barba-Sánchez (2018); Kim & Choi (2016); Poulis & Wisker (2016); Salem (2019); Widyaningdyah & Aryani (2016); Yap et al (2013) that found a positive and significant effect between environmental uncertainty and competitiveness. Likewise, environmental uncertainty has a positive and significant influence on the performance of fishing companies, consistent with research (Allegrini & Monteduro, 2018;Darvishmotevali et al, 2018;Gupta & Gupta, 2020;Harash, 2015;Hengky et al, 2018;Hosseini & Sheikhi, 2012;Kafetzopoulos et al, 2019;Mohammad, 2019;Poulis & Wisker, 2016;Widyaningdyah & Aryani, 2016;Wong et al, 2011).…”
Section: Discussion and Research Implicationssupporting
confidence: 90%
“…This finding also suggests that CI provides market insights about the competition rather than competitors (Gilad, 2016). Attesting CI provides information about competitors' present and future behaviours, customers, technologies, governments, markets, and the general business environment (Yap et al, 2013b).…”
Section: Competitionmentioning
confidence: 87%
“…The survival of organisations in the global environment depends mainly on the strategic role CI plays in establishing a highly well-designed, accurate and rigorous strategy for companies to stay ahead of their competitors (Dahou, Hacini & Bendiabdellah, 2012, p.47). This is because CI provides information about competitors' present and future behaviours, customers, technologies, governments, markets, and the general business environment (Yap et al, 2013b). CI gathers relevant information from the competitive environment to be used explicitly for planning and decision-making (Kotler et al, 2019).…”
Section: Market Factorsmentioning
confidence: 99%
See 2 more Smart Citations